solve the following equation
![0.5(2y + 9) = 0.3(4y - 6) 0.5(2y + 9) = 0.3(4y - 6)](https://tex.z-dn.net/?f=0.5%282y+%2B+9%29+%3D+0.3%284y+-+6%29)
that answer should come 63/2
Answers
Answered by
2
Step-by-step explanation:
answer is in the picture
Attachments:
![](https://hi-static.z-dn.net/files/db8/d74b72924acb78b8ef310cb49876bfc8.jpg)
Answered by
3
Answer:
6.3/0.2
Step-by-step explanation:
0.5 (2y + 9) = 0.3 (4y - 6)
= 1y + 4.5 = 1.2y - 1.8
= 4.5 + 1.8 = 2y - 1y
= 6.3 = 0.2y
•°• y = 6.3/0.5
HOPE ITS HELP YOU
Similar questions